2012
DOI: 10.1074/jbc.m111.312470
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-19 (IL-19) Induces Heme Oxygenase-1 (HO-1) Expression and Decreases Reactive Oxygen Species in Human Vascular Smooth Muscle Cells

Abstract: Heme oxygenase‐1 (HO‐1) has potent anti‐inflammatory activity and recognized vascular protective effects. We have recently described the expression and vascular protective effects of an anti‐inflammatory interleukin (IL‐19), in vascular smooth muscle cells (VSMC) and injured arteries. The objective of this study was to characterize the expression and protective effects of IL‐19‐induced HO‐1 in VSMC. HO‐1 mRNA was induced in IL‐19 stimulated cultured human VSMC, as assayed by quantitative RT‐PCR. HO‐1 protein w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
31
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 39 publications
2
31
0
Order By: Relevance
“…HO-1 is the inducible isoform of heme oxygenase that catalyzes the degradation of heme into biliverdin, iron, and carbon. HO-1 has also been shown to be an oxidative stress-responsive gene that may exert important roles in cytoprotection and the resolution of inflammation to maintain tissue homeostasis (12,38). In most cell types, HO-1 is inducible by heme, radiation, cytokines, inflammatory stimuli, and oxidative and heat stress (39).…”
Section: Phenolsmentioning
confidence: 99%
See 1 more Smart Citation
“…HO-1 is the inducible isoform of heme oxygenase that catalyzes the degradation of heme into biliverdin, iron, and carbon. HO-1 has also been shown to be an oxidative stress-responsive gene that may exert important roles in cytoprotection and the resolution of inflammation to maintain tissue homeostasis (12,38). In most cell types, HO-1 is inducible by heme, radiation, cytokines, inflammatory stimuli, and oxidative and heat stress (39).…”
Section: Phenolsmentioning
confidence: 99%
“…Biliverdin and bilirubin are potent antioxidants that attenuate oxidative stress. HO-1 has anti-inflammatory, antioxidant, and antiproliferative effects (12,13), and is induced by oxidative stress.…”
mentioning
confidence: 99%
“…Hsieh and colleagues [19], found that an alternative spliced change of IL-20 stimulated proliferation of the endothelial cells. Also, IL-19 may be used as a potential therapeutic for vascular inflammatory diseases through increased expression of heme oxygenase-1 (HO-1) and reduced reactive oxygen species in human vascular smooth muscle cells [20].…”
Section: Il-19mentioning
confidence: 99%
“…Rather, IL-19 decreases inflammatory mRNA transcript stability by inhibition of the mRNA stability factor HuR, which is known to recognize stability elements on the 3 UTR of inflammatory transcripts [133]. Also in VSMC, IL-19 induces expression of the cytoprotective and antiatherosclerotic protein heme oxygenase-1 [134]. Together, lymphocyte phenotype modulation, reduction in inflammatory transcript stability, and induction of HO-1 represent multiple novel anti-inflammatory, and potentially antiatherogenic mechanisms for IL-19.…”
Section: Il-19mentioning
confidence: 99%
“…However, recently, IL-19 has been shown to reduce angioplasty-induced restenosis in rats, and inflammatory gene expression in human VSMC [129,132]. IL-19 has also been shown to induce HO-1 expression and reduce ROS in human VSMC [134]. Together with its Th2-inducing properties, IL-19 may represent an attractive therapeutic modality to attenuate atherosclerosis.…”
Section: Upregulation Of Anti-inflammatory Cytokinesmentioning
confidence: 99%